Fabrication and anticorrosion behavior of a bi-phase TaNbHfZr/CoCrNi multilayer coating through magnetron sputtering. (March 2022) - Song, Baorui; Hua, Yong; Zhou, Chaozheng; Li, Yanhuai; Yang, Liuquan; Song, Zhongxiao
Abstract: A novel multilayer coating containing bi-phase structures was designed via a magnetron sputtering method. Surface morphologies, structure and corrosion behavior of TaNbHfZr/CoCrNi coating have been investigated via a combination of electrochemistry and surface analysis. Such bi-phase structures containing fcc CoCrNi and amorphous TaNbHfZr layers exhibited an improved corrosion resistance compared with CoCrNi monolayer coating. The hardness and elastic modulus of the TaNbHfZr/CoCrNi multilayer coating were slightly lower than the CoCrNi monolayer coating due to the softening induced by the amorphous TaNbHfZr layer, revealing that such multilayer structure possesses the desired corrosion performance and good mechanical properties. Highlights: The multilayer TaNbHfZr/CoCrNi coating contains amorphous/fcc bi-phase structure. TaNbHfZr/CoCrNi multilayer coating has higher E corr and lower i corr than the monolayer coating. The formation of thick passive film on the multilayer coating. The multilayer coating retained excellent mechanical properties. TaNbHfZr layer corrodes preferentially and accelerates the penetration of corrosive medium.